Project-based pedagogy as an alternative for the development and strengthening of communicative processes - Inostroza De Celis, Gloria (Rastros Rostros, 2024)
Education is facing a process of change caused by the high level of demands that society in general is placing on it due to the emergence of new technologies, products, ways of thinking, rhythms and capabilities.